Analisis Kadar Steroid pada Buah, Tepung dan Biskuit Labu Siam (Sechium edule) - Dina Ludin; Jamaluddin Sakung (Universitas Tadulako, 2022)
Steroids are secondary metabolites, steroid compounds can be used as antioxidant and anti-cancer compounds.This study aims to determine the levels of steroids in fruit, flour and chayote biscuits using the maceration extraction method, the determination of levels using a UV-Vis spectrophotometer. The results showed that the steroid levels in each sample were 0.235±0.03 gram/100 g, on chayote flour by 0.435±0.02 gram/100 g, and on chayote biscuits by 0.556±0.04 gram/100 g.